The Role of Relationship Factor and Institutional Factor on Link and Match Performance in Indonesia’s HEI - Gaffar, Vanessa; Sulastri, Sulastri; Supriatna, Nono; Wibowo, Lili Adi; Hendrayati, Heny; Christiyanto, Wenda Wahyu; Koeswandi, Tika Annisa (RSF Conference Series: Business, Management and Social Sciences, 2023)
The purpose of this research is to investigate the impact that institutional elements have on the effectiveness of links and matches by focusing on relationship aspects. PLS-SEM is a type of statistical analysis that is used to check hypotheses. According to the findings of the investigation, the type of mediation that took place was full mediation. According to these findings, higher education institutions (HEI) must not only pay attention to institutional aspects but also pay attention to relationship factors in order to increase link and match performance. This is despite the fact that relationship elements are vital. The aspect of the dispute that requires the most focus from HEI is one that involves fighting. HEI must be capable of keeping disagreements between partners to a minimum, and when they do arise, they must be resolved to everyone's satisfaction. According to the findings of this study, higher education institutions (HEIs) need to develop robust internals, which must be supported by robust partnerships, in order to achieve good link and match performance.